Factors Influencing Clinical Trials of Herbal Medicinal Products – Using Ginger as Example - Hook, Ingrid; Krenn, Liselotte; Steinhoff, Barbara; Wolfram, Evelyn (Planta Medica, 2025)
Ginger (Zingiber officinale) has a global use as a spice, an ingredient of beverages, food supplements (syn. dietary supplements), as well as herbal medicinal products. Since the last update of ginger in ESCOP Monographs in 2009 a significant number of papers concerning its bioactive constituents and clinical uses have been published. From this large number and selecting those references (almost 500) considered most relevant to clinical aspects and therapeutic indications, the following issues are considered to be potentially important to research on other medicinal plants: [i] quality assessment; [ii] pre-clinical (in vivo) studies; [iii] quality of clinical trials; [iv] ethnicity of clinical trial participants and [v] effects of sex-gender on activity and therapeutic indications.
Keywords: Ginger; Zingiber officinale; Zingiberaceae; factors influencing clinical trials